Reconstruction of Fetal Imaging During Pregnancy with the Electrical Impedance Imaging Technique - Kumar Konki, Sravan; Kumar Khambampati, Anil; Jung Han, You; Yob Kim, Sung; Youn Kim, Kyung (International Journal of Engineering and Technology, 2018)
Intelligent fetal imaging techniques are required to monitor the development of fetal growth and fetal condition during pregnancy period. Conventional fetal imaging techniques such as fetal ultrasound and Cardiotocogram (CTG) are expensive and uncomfortable to the patient. In this study, we developed an electrical impedance tomography (EIT) imaging method to reconstruct fetal images. EIT is a non-invasive and  low cost medical imaging technique that reconstructs the internal resistivity distribution of fetus by injecting electrical currents and measure the resulting voltages through the electrodes which are placed on the boundary of pregnant abdomen. Finite element method (FEM) used as an EIT forward solver and  inverse solver based on Newton-Raphson method with Tikhonov regularization is used to estimate the electrical resistivity distribution of the fetus inside the pregnant abdomen. To investigate the performance of proposed EIT fetal imaging method, we performed numerical simulations with different locations of fetus in the pregnant abdomen shaped mesh.  Numerical simulation results are shown that the EIT imaging with Newton-Raphson method (mNR) could be applied to the fetal imaging during pregnancy period.